Konsep Tanggung Jawab Orang Tua dalam Pendidikan Anak Perspektif Surat At-Tahrim Ayat 6 - M Khoir Alkusyairi; Nining Suniarti (EL-EMIR Institute, 2026)
Family education plays a crucial role in shaping a child's character, morals, and faith. However, technological advancements, promiscuity, and a lack of parental attention to religious education have led to a decline in children's morals. This situation highlights the importance of understanding parental responsibility in educating children based on Islamic teachings. This study aims to understand the concept of parental responsibility in educating children from the perspective of Surah At-Tahrim, verse 6, and to analyze the implementation of its educational values ​​in family life. This study employed a qualitative approach with library research. Data were obtained from the Quran, hadith, tafsir (comprehension texts), books, and scientific journals relevant to the research theme. Content analysis was used as the data analysis technique. The results show that Surah At-Tahrim, verse 6, emphasizes parents' responsibility in safeguarding the family through education in faith, worship, morals, role models, and supervision of children. The implementation of these educational values ​​can shape a generation of faithful, pious, and noble characters in accordance with Islamic teachings.